Pengaruh Likuiditas, Leverage, Profitabilitas, dan Investasi Berkelanjutan Terhadap Nilai Perusahaan pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2020–2024 - Putri Utami Wijayati; Sobrotul Imtikhanah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to examine the impact of liquidity, debt, profitability, and sustainable investment on firm value in manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the 2020–2024 period. Firm value is a very important indicator that reflects investors' views on a company's performance and long-term prospects. The research sample consisted of 27 manufacturing companies that were purposively selected based on certain criteria, such as data availability and consistency in financial reporting over five years, resulting in a total of 135 observational data. This study uses a quantitative approach by applying multiple linear regression analysis to investigate the relationship between the independent and dependent variables. The analysis results show that, simultaneously, all four independent variables have a significant impact on firm value, as evidenced by an F value of 9.145 and a significance level of 0.000. However, separately, only the profitability variable has a positive and significant impact on firm value (sig. = 0.000). In contrast, the liquidity, debt, and sustainable investment variables do not show a significant impact on firm value in the model used.